Cave species of the genus Anurida (Collembola: Neanuridae) from Korea, with the description of new species - Lee, Inae; Park, Kyung-Hwa (Zootaxa, 2016)
Three troglobiontic species of Anurida Laboulbène, i.e. A. troglodyta sp. nov., A. decipiens Yosii, 1966, and A. plurichaetotica Yosii, 1966, were found in limestone caves of Korea during recent investigation. The new species, A. troglodyta sp. nov., is characterized by morel-like PAO having more than 100 vesicles and by having 16–17 sensilla on antennal segment IV. It is most similar to A. plurichaetotica, A. okamotoi Yosii, 1970, and A. irieti Yosii, 1970 also possessing several macrochaetae on dorsal side of a head, but can easily be distinguished by characteristic PAO and the absence of macrochaetae in p1-position on abdominal tergum V. A. decipiens is redescribed based on new material from the cave of the types’ origin.